THE INFLUENCE OF STRATEGIC MANAGEMENT ON FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES (JAVA REGION) - Sari Bulan Tambunan (SEAN Institute, 2023)
Study This is done to know if application of strategic management is influential and significant to performance finances in the company manufacturing, and to know which variable has the most dominant influence on performance in the company manufacturing (Java Region). Population study This is a manufacturing company that uses the purposive sampling method, and those that comply can receive as many as 30 samples. Data used with primary data via the Stock Exchange Indonesian for implementation of strategy management and performance of company finance for the connection between variables, a statistical test was carried out using linear regression with SPSS stone tools. Research results show that application of strategic management against performance company finance manufacture including in category medium Statistical test results found that there is a positive and significant connection between application strategic management and performance company finance manufacturing. As for the variables that have the most dominant influence on the performance of companies manufacturing in Indonesia, profitability Research results This should become input for holder interest in increasing competence perpetrator business in face competition effort.